Influence of Operating Parameters on Performance of Air-assisted Garlic Clove Peeler - Mudgal, V D; Chapawat, P S (Journal of Agricultural Engineering, 2008)
Garlic (Alliums sativum L.) is being used as a food, a condiment, and for medicinal purposes in many centuries. Garlic bulbs contain crude protein, crude oil, crude fiber, ash, dimethyl sulphite (DMS) and essential oil and minerals. The peeling of garlic cloves requires special care and skill, due to the typical physical characteristics and presence of essential volatile oils in the epidermal cells imparting garlic its characteristic aroma. Conventional method of peeling is very laborious and unhygienic. Considering the increasing demand for garlic products in domestic and export market, a low cost garlic clove peeler was developed and its performance was evaluated. The height of the peeling chamber (400 mm), bed depth (60 mm), air jet pressure (10, 15 and 20 kg/cmÂ²) and the position of air jet (60, 80 and 90 mm) were taken for evaluation. The peeling efficiency was observed to be 97-98%.